PTU-148 Healthcare Costs And Quality Of Life Associated With Acute Upper Gastrointestinal Bleeding In The Uk. (9th June 2014) - Stokes, E; Campbell, H; Bargo, D; Murphy, M; Logan, R; Jairath, V
Abstract : Introduction: Acute upper gastrointestinal bleeding (AUGIB) accounts for over 70, 000 hospital admissions in the UK annually. Its incidence is likely to rise due to an ageing population and increasing burden of liver disease. Data on the healthcare costs and health-related quality of life (HRQoL) associated with this condition are sparse. Methods: The TRIGGER trial is a cluster randomised feasibility trial evaluating restrictive versus liberal red cell transfusion for patients with AUGIB. The study collected data on resource use, costs and outcomes during hospitalisation and up to day 28 to explore the feasibility of gathering inputs required for a cost-effectiveness analysis. Resource use data were collected during the inpatient episode on the use of laboratory tests, medications, blood components, endoscopy and endoscopic therapy, clinical events including ischaemic/thromboembolic events and length of hospital stay (LOS) by ward type. Data were also collected on primary and secondary care resource use, as well as informal care/days off work, post-discharge to day 28. Resource use for each patient was multiplied by national unit costs to generate an estimate of the costs of AUGIB to 28 days. HRQoL was measured on a scale anchored at 0 (death) and 1 (full health), using the EuroQol EQ-5D-3L questionnaire at day 28. Results: 936 patients were enrolled into TRIGGER between August 2012 and March 2013 in 6 UK hospitals. Preliminary analyses show that the mean (standard error (SE)) cost of the inpatient episode was £1, 914 (£78) per patient. LOS was a key cost driver; mean LOS was 5.4 days with an associated cost of £1431. Additional cost drivers included: (1) red cell transfusion, with a mean of 1.6 units transfused per patient at a cost of £197; (2) endoscopy, with mean of 0.8 endoscopies per patient at a cost of £169. Mean (SE) costs from hospital discharge to 28 days were £293 (£22) per patient. The main cost driver post discharge was readmission to hospital; 12% of patients were readmitted within 28 days for a mean of 4.8 days. The mean cost associated with readmission across all patients was £127. HRQoL was on average (SE) 0.68 (0.01) at 28 days. Conclusion: The mean cost up to 28 days for patients presenting with AUGIB is £2, 207. At 28 days, the mean HRQoL in patients who have experienced an AUGIB is well below the average population level of 0.86. This is the first study to provide detailed estimates of the costs and HRQoL associated with AUGIB in the UK. These data can be used by healthcare providers and researchers to inform the design of subsequent cost-effectiveness analyses of interventions for AUGIB. Disclosure of Interest: None Declared.